A Contrastive Study of English and Arabic Multi-Word or Two-word Verbs in Selected Novels - Nasir, Kamal G; Husain, Hasan Ali (International Journal of Psychosocial Rehabilitation, 2020)
The present study is concerned with a linguistic contrastive analysis of one characteristic of grammar and vocabulary in English and Arabic languages which is combinations of lexical verbs with adverbial and/or prepositional particle(s), which are commonly known as: Multi-word verbs; Two-Word verbs or PVs (晦䁚ꀀ ᦙ䁡ꀀ香 ommo香). In addition, the study attempts to prove that there are fundamental similarities and dissimilarities between English and Arabic multi-word verbs. Such similarities and dissimilarities are investigated at length through a theoretical comparison of these combinations in both languages and through the analysis of two selected novels below. The present study falls into five sections as follows: it starts with an introductory section where an introduction of the notion of multi-word verbs in both languages is provided followed by section two and three which are devoted to the theoretical backgrounds of the multi-word verbs in English and Arabic respectively. Section four is the analysis of the target verbs in English novel (East of Eden) by Steinbeck (1952) and Arabic novel (Palace of Desire) [Qaṣr ãl shawq] by Maḥfũẓ (1957). And section five reveals the conclusions and results